Griscelli syndrome type 2: Rare 3 cases from Iraq - Mouroge Hashim AL Ani; Farah Samer Yahya (Iraqi Journal of Hematology)
Griscelli syndrome (GS) is multisystem disorder of three subtypes, hereditary autosomal recessive diseases characterized by inborn silvery gray hair, partial skin albinism & immune deficiency. It was first reported by Griscelli et al. in 1978. The pathogenic defect in the RAB27Agene is responsible both for inborn pigmentary impairment and for triggering the Hemophagocytic lymphohistiocytosis (HLH) a rapidly progressive, life-threatening condtion. We present two cases from different governorates who were diagnosed with GS by achieving genetic study: the first case was saved by successful bone marrow transplantation, whereas the second case died before managing to do the procedure, being rare and underdiagnosed disease end with misdiagnosis and mismanagement.